0

# 5(3x-6)=6(2x-3)

I would love it if you went into absolute detail.

### 1 Answer by Expert Tutors

John R. | John R: Math, Science, and History TeacherJohn R: Math, Science, and History Teach...
4.6 4.6 (55 lesson ratings) (55)
2

5(3x - 6) = 6(2x - 3)                 Given

5(3x) - 5(6) = 6(2x) - 6(3)         Distributive property

15x - 30 = 12x - 18                   Simplify

15x - 30 + 30 = 12x - 18 + 30    Add 30 to each side

15x + 0 = 12x - 18 + 30            Inverse property of addition

15x = 12x - 18 + 30                  Identity property of addition

15x = 12x + 12                         Simplify

15x - 12x = 12x + 12 - 12x        Subtract 12x from each side

15x - 12x = 12 + 0                    Inverse property of addition

15x - 12x = 12                          Identity property of addition

3x = 12                                    Simplify

3x/3 = 12/3                              Divide each side by 3

1x = 12/3                                 Inverse property of multiplication

x = 12/3                                   Identity property of multiplication

x = 4                                       Simplify